The Urgency of Reforming Electric Bicycle Regulations in Indonesia in Providing Legal Certainty - Khairunnisa, Khairunnisa; Hasibuan, Khairuna Malik; Saviera, Lesly; Yulistari, Faradila (TATOHI: Jurnal Ilmu Hukum, 2026)
Introduction: The increasing popularity of e-bikes in Indonesia has not been offset by comprehensive regulations, creating safety risks. Law Number 22 of 2009 has not explicitly classified electric bicycles, while Regulation of the Minister of Transportation Number 45 of 2020, although regulating technicalities and areas of use, is still limited to the absence of clear violation sanctions, including for underage users. Purposes of the Research: Analyze the importance of electric bicycle regulation in Indonesia by examining the existing regulations in Law Number 22 of 2009 and Regulation of the Minister of Transportation Number 45 of 2020, and identifying the urgency of strengthening regulations. Methods of the Research: Using normative legal research methods with a legislative approach. Findings of the Research: This study found that the Minister of Transportation Regulation Number 45 of 2020 only covers the definition, requirements for completeness, and areas of use of electric bicycles, but does not regulate the sanctions for violations in detail. This legal vacuum hinders law enforcement and safety assurance. Therefore, strengthening regulations through stricter safety standards and strict sanctions is very urgent to minimize traffic accidents and provide legal certainty.